en - Rachmah, Zakia; Widya, Widya; Putri, Evi Jovita (e-Journal of Linguistics; Vol 16 No 2 (2022): ejl-July, 2022)
This research determines types of non-observance of maxim in influencing the implicatures arose and analyze the implicatures in characters' utterances. This is library research in which the data are collected from a movie script and presented in a qualitative descriptive approach. The subject of this study is the Cruella movie that was released in 2021. The data are obtained by watching, screenshotting the scenes, reading the script and highlighting the utterances. In executing the data, firstly is identifying the data, secondly explaining the context, thirdly examining the non-adherence to the maxim in those utterances, finally analyzing the implicatures based on the context. The main theory used is from Grice in (Yule, 1996) and (Thomas, 2013). Based on the theories used, it was found 4 types of non-observance of maxim: flouting (26), violating (7), suspending (4) and opting out (1). Flouting is the way frequently used by the speaker because the characters had other meanings and or additional meaning to be conveyed in delivering the message indirectly. The maxim frequently not adhered is maxim of quality. Hence, it is found conversational implicature: generalized (8) and particularized (30). According to the implicature, there are some negative values that related to issue of the movie, they are theft, lying, rude sarcasm, killing and sabotage.